WC-Co-Ti3AlC2 hard alloy and preparation method and application thereof

Through the preparation method of WC-Co-Ti3AlC2 cemented carbide, the serious wear problem of WC-Co cemented carbide in mechanical processing is solved, the hardness and wear resistance are improved, the friction coefficient and wear amount are reduced, and the service life is extended , and achieves process stability and suitable large-scale production.

CN119242976APending Publication Date: 2025-01-03LINGNAN NORMAL UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411381749.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-30
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

WC-Co carbide is seriously worn in application environments such as machining, resulting in tool failure, and the prior art is difficult to meet the high requirements of its hardness and wear resistance.

Method used

Using the preparation method of WC-Co-Ti3AlC2 carbide, hard materials with high hardness and wear resistance are prepared by mixing tungsten carbide powder, cobalt powder and Ti3AlC2 powder and wet grinding, drying, pressing and argon sintering. alloy.

Benefits of technology

It improves the hardness and wear resistance of cemented carbide, reduces the friction coefficient and wear amount, extends the service life, and is stable, simple and easy to use, and is suitable for mass production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119242976A_ABST
    Figure CN119242976A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of hard alloy preparation, in particular to a WC-Co-Ti3AlC2 hard alloy and a preparation method and application thereof. Comprising the steps that tungsten carbide powder, cobalt powder, Ti3AlC2 powder and a forming agent are mixed and then subjected to wet grinding and drying, and hard alloy mixed powder is obtained; pressing the hard alloy mixed powder to obtain a green body; and the green body is sintered in the argon atmosphere, and the WC-Co-Ti3AlC2 hard alloy is obtained. According to the prepared ultra-fine grain wear-resistant WC-Co-Ti3AlC2 hard alloy, the hardness of the hard alloy is improved, the friction coefficient and the abrasion loss are reduced, and the service life of the hard alloy material is prolonged. The hard alloy prepared through the method is stable in process, simple and feasible in method, high in repeatability and suitable for mass production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of cemented carbide preparation, and in particular to a WC-Co-Ti3AlC2 cemented carbide and a preparation method and application thereof. Background Art

[0002] Cemented carbide has extremely high hardness, toughness, good wear resistance, heat resistance, and corrosion resistance, which makes cemented carbide have a wide range of application environments, such as: military industry, aerospace, mechanical processing, metallurgy, oil drilling, mining tools, electronic communications, construction and other fields. Among cemented carbides, tungsten-cobalt cemented carbide is the most widely used. It is composed of tungsten carbide (WC) particles and cobalt (Co) used to bond WC. The phase properties (wetting angle, solubility, etc.) between the hard phase WC grains and the bonding phase Co make tungsten-cobalt cemented carbide have superior mechanical properties and friction and wear properties. The modern and mature preparation process also makes it have lower costs and a larger market.

[0003] During use, the wear of WC-Co cemented carbide materials is an issue that needs to be considered, especially in application environments such as mechanical processing. Wear is the main failure mode of cemented carbide tools, so higher requirements are placed on the hardness and wear resistance of cemented carbide materials. Summary of the invention

[0004] In order to solve the above problems, the present invention provides a WC-Co-Ti3AlC2 cemented carbide and a preparation method and application thereof. The cemented carbide prepared by the preparation method provided by the present invention has the characteristics of high hardness and good wear resistance.

[0005] In order to achieve the above object, the present invention provides the following technical solutions:

[0006] The present invention provides a method for preparing a WC-Co-Ti3AlC2 cemented carbide, comprising the following steps:

[0007] 1) mixing tungsten carbide powder, cobalt powder, Ti3AlC2 powder and a forming agent, wet grinding and drying to obtain a cemented carbide mixed powder;

[0008] 2) pressing the cemented carbide mixed powder obtained in step 1) to obtain a green body;

[0009] 3) Sintering the green body obtained in step 2) under an argon atmosphere to obtain WC-Co-Ti3AlC2 cemented carbide.

[0010] Preferably, in step 1), the mass ratio of tungsten carbide powder, cobalt powder and Ti3AlC2 powder is 90.5-91.5:8:0.5-1.5.

[0011] Preferably, the mass ratio of the tungsten carbide powder, cobalt powder and Ti3AlC2 powder is 91:8:0.5-1.

[0012] Preferably, the conditions of wet grinding in step 1) include: the molding agent includes polyethylene glycol, paraffin or rubber, and the added amount is 1 to 3% of the total mass of tungsten carbide powder, cobalt powder and Ti3AlC2 powder;

[0013] The wet grinding media used include anhydrous ethanol or dimethyl ketone, the ball-to-material ratio is 6 to 15:1, the rotation speed is 250 to 500 rpm, and the time is 24 to 72 hours.

[0014] Preferably, the drying conditions in step 1) include: a temperature of 70 to 80° C. and a drying time of 5 to 12 hours.

[0015] Preferably, the pressing conditions in step 2) include: a pressure of 200 to 350 MPa and a pressing time of 30 to 150 s.

[0016] Preferably, the sintering conditions in step 3) include: a temperature of 1330 to 1480° C. and a time of 30 to 120 min.

[0017] The present invention also provides a WC-Co-Ti3AlC2 hard alloy prepared by the preparation method described in the above technical solution.

[0018] The present invention also provides the use of the WC-Co-Ti3AlC2 cemented carbide described in the above technical solution in improving the hardness of the cemented carbide.

[0019] The present invention also provides the use of the WC-Co-Ti3AlC2 cemented carbide described in the above technical solution in reducing the friction coefficient and / or wear amount of the cemented carbide.

[0020] Beneficial effects of the present invention:

[0021] The ultrafine-grained wear-resistant WC-Co-Ti3AlC2 hard alloy prepared by the present invention improves the hard alloy hardness, reduces the friction coefficient and the wear amount, and improves the service life of the hard alloy material. The hard alloy prepared by the present invention has a stable process, a simple and easy method, strong repeatability, and is suitable for mass production. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required to be used in the embodiments are briefly introduced below.

[0023] Figure 1 The friction coefficient of Examples 1-3 and Comparative Example 1 varies with time;

[0024] Figure 2It is a comparison diagram of the wear profiles of Examples 1-3 and Comparative Example 1;

[0025] Figure 3 The wear scar morphologies of Examples 1-3 and Comparative Example 1, wherein a: Comparative Example 1; b: Example 1; c: Example 2; d: Example 3. DETAILED DESCRIPTION

[0026] The present invention provides a method for preparing a WC-Co-Ti3AlC2 cemented carbide, comprising the following steps:

[0027] 1) mixing tungsten carbide powder, cobalt powder, Ti3AlC2 powder and a forming agent, wet grinding and drying to obtain a cemented carbide mixed powder;

[0028] 2) pressing the cemented carbide mixed powder obtained in step 1) to obtain a green body;

[0029] 3) Sintering the green body obtained in step 2) under an argon atmosphere to obtain WC-Co-Ti3AlC2 cemented carbide.

[0030] The present invention mixes tungsten carbide powder, cobalt powder, Ti3AlC2 powder and a forming agent, and then wet-grinds and dries to obtain a cemented carbide mixed powder. In the present invention, the mass ratio of the tungsten carbide powder, cobalt powder and Ti3AlC2 powder is preferably 90.5-91.5:8:0.5-1.5. In the present invention, the mass ratio of the tungsten carbide powder, cobalt powder and Ti3AlC2 powder is preferably 91:8:0.5-1. In the present invention, the particle size of the tungsten carbide powder is preferably 0.2 μm. In the present invention, the particle size of the cobalt powder is preferably 0.5 μm. In the present invention, the particle size of the Ti3AlC2 powder is preferably 3 μm.

[0031] The present invention uses tungsten carbide powder as a cemented carbide base material. The present invention uses cobalt powder as a cemented carbide binder phase. The present invention uses Ti3AlC2 powder as a grain growth inhibitor, and utilizes its self-lubricating property to make the prepared cemented carbide have high hardness and high wear resistance, thereby extending the service life of the cemented carbide.

[0032] In the present invention, the wet grinding conditions preferably include: the molding agent preferably includes polyethylene glycol, paraffin or rubber, and the addition amount is preferably 1-3% of the total mass of tungsten carbide powder, cobalt powder and Ti3AlC2 powder; the wet grinding medium used preferably includes anhydrous ethanol or dimethyl ketone, the ball-to-material ratio is 6-15:1, the rotation speed is 250-500rpm, and the time is 24-72h. The purpose of the mixed wet grinding in the present invention is to completely mix the cemented carbide raw material powder.

[0033] In the present invention, the drying conditions preferably include: a temperature of 70 to 80°C and a time of 5 to 12 hours. The present invention dries the cemented carbide raw material mixture after wet grinding, and the drying equipment is a vacuum rotary evaporator. The purpose of drying in the present invention is to evaporate the ball milling media in the cemented carbide raw material mixture.

[0034] The present invention presses the obtained cemented carbide mixed powder to obtain a green body. In the present invention, the pressing conditions preferably include: a pressure of 200-350 MPa and a time of 30-150 seconds. The purpose of the molding in the present invention is to obtain a green body of a desired shape and size.

[0035] The present invention sintered the obtained green body in an argon atmosphere to obtain WC-Co-Ti3AlC2 cemented carbide. In the present invention, the sintering conditions preferably include: a sintering temperature of 1330-1480°C and a time of 30-120 minutes. The present invention preferably performs high-temperature liquid phase sintering on the green body in an argon atmosphere, and the vacuum degree of the high-temperature liquid phase sintering is 10 -3 ~10 -2 Pa, the sintering temperature is 1330-1480°C, the temperature is increased from room temperature to 1200°C at a rate of 10°C / min, the vacuum system is closed, argon gas is introduced with a pressure of 0.5-5MPa, and the temperature is increased to the sintering temperature at a rate of 3.6°C / min, and then kept warm for 30-120min, and finally cooled to room temperature with the furnace to obtain WC-Co-Ti3AlC2 cemented carbide.

[0036] The present invention promotes the shrinkage behavior of cemented carbide during liquid phase sintering and prevents the volatilization of Co phase through argon atmosphere protection and selection of appropriate sintering temperature, thereby improving the hardness of cemented carbide; the present invention uses Ti3AlC2 as an additive to dope WC-Co cemented carbide, and TiC decomposed from Ti3AlC2 at high temperature is a significant grain growth inhibitor, which can refine WC grains, thereby improving the hardness of cemented carbide; as a layered material, Ti3AlC2 has self-lubricity, and after improving the hardness of cemented carbide, the depth of the abrasive indentation can be reduced, thereby reducing the contact area, thereby achieving the purpose of improving the wear resistance of cemented carbide.

[0037] The present invention also provides a WC-Co-Ti3AlC2 hard alloy prepared by the preparation method described in the above technical solution.

[0038] The present invention also provides the use of the WC-Co-Ti3AlC2 cemented carbide described in the above technical solution in improving the hardness of cemented carbide.

[0039] The present invention also provides the use of the WC-Co-Ti3AlC2 cemented carbide described in the above technical solution in reducing the friction coefficient and / or wear amount of the cemented carbide.

[0040] The WC-Co-Ti3AlC2 hard alloy prepared by the technical solution of the present invention has a hardness of 1800-2150kgf / mm 2 The average friction coefficient in the steady state stage is 0.46-0.6, and the wear rate is reduced by 13-50% compared with WC-Co cemented carbide.

[0041] In order to further illustrate the present invention, the present invention is described in detail below in conjunction with embodiments, but they should not be construed as limiting the scope of protection of the present invention.

[0042] Example 1

[0043] The cemented carbide raw material powder is mixed according to the following mass fractions: WC powder 91.5%, Co powder 8.0%, Ti3AlC2 powder 0.5%, and the powder particle sizes are 0.2μm, 0.5μm, and 3μm respectively;

[0044] Preparation method:

[0045] The cemented carbide raw material was mixed with 2wt% (mass ratio of polyethylene glycol to cemented carbide raw material) polyethylene glycol, and the mixed materials were wet-milled for 48 hours, the medium was anhydrous ethanol, the ball-to-material ratio was 10:1, and the rotation speed was 325 rpm;

[0046] After the wet grinding of the mixed materials is completed, the cemented carbide mixed liquid is placed in a vacuum rotary evaporator for drying at a temperature of 75°C for a drying time of 10 hours to obtain a cemented carbide mixed raw material;

[0047] The cemented carbide mixed raw material was molded at a molding pressure of 320 MPa and a holding time of 60 seconds to obtain a cylindrical green body with a molding diameter of 10 mm and a height of 10 mm;

[0048] The green body was placed in a high temperature and high vacuum atmosphere furnace for liquid phase sintering. -3 ~2.0×10 -2 Pa conditions, the temperature was raised from room temperature to 1200°C at a rate of 10°C / min, the vacuum system was closed, argon gas was introduced with a pressure of 2MPa, and the temperature was raised to the sintering temperature of 1400°C at a rate of 3.6°C / min and kept warm for 60min. After the insulation was completed, the furnace was cooled to room temperature to obtain ultrafine-grained wear-resistant WC-Co-0.5Ti3AlC2 cemented carbide.

[0049] Example 2

[0050] The difference between this embodiment and embodiment 1 is that the cemented carbide raw material powder is mixed according to the following mass fraction ratio: WC powder 91.0%, Co powder 8.0%, Ti3AlC2 powder 1.0%, and the powder particle sizes are 0.2μm, 0.5μm, and 3μm respectively, to obtain ultrafine-grained wear-resistant WC-Co-1.0Ti3AlC2 cemented carbide.

[0051] Example 3

[0052] The difference between this embodiment and embodiment 1 is that the cemented carbide raw material powder is mixed according to the following mass fraction ratio: WC powder 90.5%, Co powder 8.0%, Ti3AlC2 powder 1.5%, and the powder particle sizes are 0.2μm, 0.5μm, and 3μm respectively, to obtain ultrafine-grained wear-resistant WC-Co-1.5Ti3AlC2 cemented carbide.

[0053] Comparative Example 1

[0054] The present embodiment is different from the embodiment 1 in that the cemented carbide raw material powders are mixed according to the following mass fraction ratios: WC powder 92.0%, Co powder 8.0%, and the powder particle sizes are 0.2 μm and 0.5 μm respectively, to obtain WC-Co cemented carbide.

[0055] Performance Testing

[0056] Chapter 1 The hard alloys prepared in Examples 1-3 and Comparative Example 1 were tested using GB_T 7997-2014 "Test Method for Vickers Hardness of Hard Alloys" and JB T 12616-2016 "Test Method for Fracture Toughness of Hard Alloy Tool Matrix Materials". The results are shown in Table 1 Figure 1 and Figure 2 It can be concluded from the figure that the ultrafine-grained wear-resistant WC-Co-Ti3AlC2 cemented carbide prepared by the present invention can improve the hardness of the cemented carbide and ensure that the fracture toughness is slightly reduced.

[0057] Reciprocating friction test was conducted on Examples 1-3 and Comparative Example 1. The load of the reciprocating friction test was 50N, the friction speed was 0.083m / s, and the friction time was 60min. The relationship between the friction coefficient and time was obtained as follows: Figure 1 As shown in Table 2, the average friction coefficient in the steady state stage is given by Figure 1 As shown in Table 2, the ultrafine-grained wear-resistant WC-Co-Ti3AlC2 cemented carbide prepared by the present invention can reduce the friction coefficient of WC-Co cemented carbide; the two-dimensional wear profiles of the wear scar surfaces of different examples and the actual wear scar morphologies are shown in Figure 2 and Figure 3 As shown in the figure, it can be seen that the wear scar depth of the ultrafine-grained wear-resistant WC-Co-Ti3AlC2 cemented carbide prepared by the present invention is shallower than that of the WC-Co cemented carbide.

[0058] Table 1 Mechanical properties of comparative example 1 and examples 1-3

[0059] Example <![CDATA[Hardness (kgf / mm 2 )]]> <![CDATA[Fracture toughness (MPa·m 1 / 2 )]]> Comparative Example 1 1837.00±20.22 8.63±0.16 Example 1 2007.50±11.65 8.54±0.14 Example 2 2130.12±13.58 8.45±0.16 Example 3 2011.61±32.78 8.14±0.17

[0060] Table 2 Average friction coefficient of comparative example 1 and examples 1-3

[0061] Example Average friction coefficient Comparative Example 1 0.612±0.016 Example 1 0.515±0.101 Example 2 0.462±0.009 Example 3 0.552±0.016

[0062] It can be seen from the above embodiments that the present invention provides a method for preparing ultrafine-grained wear-resistant WC-Co-Ti3AlC2 cemented carbide. The ultrafine-grained wear-resistant WC-Co-Ti3AlC2 cemented carbide prepared by the present invention has a hardness of 1900-2150 kgf / mm 2 , the average friction coefficient in the steady state stage is 0.46-0.6. Compared with the comparative example, the hardness is increased by 19.4%, the average friction coefficient in the steady state stage is reduced by 23.3%, and the wear rate is reduced by 47.4%. The ultrafine-grained wear-resistant WC-Co-Ti3AlC2 cemented carbide prepared by the present invention has the characteristics of high hardness and high wear resistance, and the preparation process is simple and easy to operate, the raw materials and equipment are relatively economical, the preparation cost is low, and it is suitable for large-scale production.

[0063] Although the above embodiment describes the present invention in detail, it is only a part of the embodiments of the present invention, not all of the embodiments. People can also obtain other embodiments based on this embodiment without creativity, and these embodiments all fall within the protection scope of the present invention.

Claims

1. A method for preparing WC-Co-Ti3AlC2 cemented carbide, characterized in that: The following steps are involved: 1) mixing tungsten carbide powder, cobalt powder, Ti3AlC2 powder and a forming agent, wet grinding and drying to obtain a cemented carbide mixed powder; 2) pressing the cemented carbide mixed powder obtained in step 1) to obtain a green body; 3) Sintering the green body obtained in step 2) under an argon atmosphere to obtain WC-Co-Ti3AlC2 cemented carbide.

2. The preparation method according to claim 1, characterized in that: In the step 1), the mass ratio of tungsten carbide powder, cobalt powder and Ti3AlC2 powder is 90.5-91.5:8:0.5-1.

5.

3. The preparation method according to claim 1 or 2, characterized in that: The mass ratio of the tungsten carbide powder, cobalt powder and Ti3AlC2 powder is 91:8:0.5-1.

4. The preparation method according to claim 1, characterized in that: The conditions of wet grinding in step 1) include: the molding agent includes polyethylene glycol, paraffin or rubber, and the addition amount is 1-3% of the total mass of tungsten carbide powder, cobalt powder and Ti3AlC2 powder; The wet grinding media used include anhydrous ethanol or dimethyl ketone, the ball-to-material ratio is 6 to 15:1, the rotation speed is 250 to 500 rpm, and the time is 24 to 72 hours.

5. The preparation method according to claim 1, characterized in that: The drying conditions in step 1) include: a temperature of 70 to 80° C. and a drying time of 5 to 12 hours.

6. The preparation method according to claim 1, characterized in that: The pressing conditions in step 2) include: a pressure of 200 to 350 MPa and a pressing time of 30 to 150 seconds.

7. The preparation method according to claim 1, characterized in that: The sintering conditions of step 3) include: a temperature of 1330 to 1480° C. and a sintering time of 30 to 120 minutes.

8. A WC-Co-Ti3AlC2 cemented carbide prepared by the preparation method according to any one of claims 1 to 7.

9. Use of the WC-Co-Ti3AlC2 cemented carbide according to claim 8 in improving the hardness of cemented carbide.

10. Use of the WC-Co-Ti3AlC2 cemented carbide according to claim 8 in reducing the friction coefficient and / or wear amount of cemented carbide.